Cancer Immunotherapy, Part 2: Efficacy, Safety, and Other Clinical Considerations - Ventola, C. Lee (P T, 2017)
The understanding of the relationship between cancer and the immune system has progressed rapidly in recent decades.1–3 The efficacy of many cancer immunotherapies, such as monoclonal antibodies, cytokines, cancer vaccines, and cell-based therapies, has been demonstrated, allowing these treatments to be incorporated into clinical practice.1,3–8 However, in some cancers and some patients, the success of cancer immunotherapy agents that target single molecular abnormalities or cancer survival mechanisms has been limited to clinical responses and modestly better survival.1,2 To improve outcomes, combination treatments with cancer immunotherapy agents may be necessary.1–3,6,9,10 This article provides an overview of the efficacy and safety of cancer immunotherapies, including additional clinical considerations regarding immune checkpoint blockers (ICBs).3,11–17